The Effect of Tax Expenses, Profit Volatility, and Cash Holding on the Quality of Profits of Companies in the Basic Industry and Chemical Sectors - Azzahra, Azzahra; Suhardi, Suhardi; Amin, Mat (Lembaga Riset Mutiara Akbar (LARISMA), 2025)
The quality of profits acts as a mediator in conflicts of interest between management and capital owners, with its main function as an indicator of performance and the basis for investment decision-making. The pressure to maintain a positive performance image can prompt management to respond to tax expenses, profit fluctuations, and manage cash strategically, potentially impacting the reliability of financial information. This study analyzes the influence of tax expenses, profit volatility, and cash holding on the quality of profits of companies in the basic and chemical industries sectors listed on the Indonesia Stock Exchange as industries experiencing a significant performance surge in 2023–2024. This phenomenon was statistically analyzed in a quantitative approach of panel data regression analysis of 165 observations from 33 companies, using Common Effect Model (CEM). The results show that separately, tax expense has a negative and significant effect on profit quality, while profit volatility and cash holding have no significant effect. Simultaneously, all three variables have a significant effect, with tax burden as the dominant factor. The results of the test imply the importance of focusing on corporate fiscal pressures as it can impact the integrity of earnings reporting, which is closely related to investor perceptions and decisions.